2018
DOI: 10.3389/fmicb.2018.01917
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Host-Derived Glycans by Intestinal Lactobacillus and Bifidobacterium Species

Abstract: Members of the genus Lactobacillus are commonly found at the gastrointestinal tract and other mucosal surfaces of humans. This genus includes various species with a great number of potentially probiotic bacteria. Other often-used probiotic species belong to Bifidobacterium, a genus almost exclusively associated with the gut. As probiotics must survive and be metabolically active at their target sites, namely host mucosal surfaces, consumption of host-produced glycans is a key factor for their survival and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 151 publications
3
70
0
1
Order By: Relevance
“…In animals, the glycoproteins facilitate the growth of probiotics in the gut thus provides a chemical barrier against pathogens [93]. The O-glycans of glycoproteins like MUC2 can serve as attachment sites for probiotic colonization [13,94] by providing favorable nutrition substances [95]. Consequently, intestinal surface harbors a complex ecosystem consisting of a myriad of intestinal microorganisms that affect the physiology, immune function, and fitness of the host [96].…”
Section: Chemical Barriermentioning
confidence: 99%
“…In animals, the glycoproteins facilitate the growth of probiotics in the gut thus provides a chemical barrier against pathogens [93]. The O-glycans of glycoproteins like MUC2 can serve as attachment sites for probiotic colonization [13,94] by providing favorable nutrition substances [95]. Consequently, intestinal surface harbors a complex ecosystem consisting of a myriad of intestinal microorganisms that affect the physiology, immune function, and fitness of the host [96].…”
Section: Chemical Barriermentioning
confidence: 99%
“…longum (B. longum), are frequently detected in the stool of breast-fed infants. Many studies [9][10][11][12][13][14][15][16][17][18][19] have indicated that the formation of a bifidus-flora in the gut of breast-fed infants can be attributed to human milk oligosaccharides (HMOs), which are the third most abundant solid component in breastmilk after lactose and lipids [20][21][22]. Mothers produce the energy-rich HMOs, even though HMOs have no direct nutritional value for infants, as HMOs are resistant to digestive enzymes secreted in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…N-Glycosylated proteins are present at human mucosal surfaces and in breast milk (9,10,52), and therefore, they can be accessible to the gut microbiota. Most studies about energy sources for gut-beneficial microbes have been focused on carbohydrates present in the diet or added as prebiotics (53), whereas knowledge about the catabolism of host-derived carbon and nitrogen sources is scarce (16). We have demonstrated that L. casei is able to metabolize the glycoamino acid 6=FN-Asn, which is the core structure of the N-glycan sites of ␣1,6-fucosylated glycoproteins.…”
Section: Discussionmentioning
confidence: 95%
“…Protein N-glycosylation plays a crucial role in a variety of cellular processes, such as cell adhesion (13), immune pathway signaling (14), and bacterial recognition (15). Some intestinal microorganisms have the ability to process the carbohydrate moieties of N-glycosylated proteins (16) so that the type, abundance, and location of these glycans contribute to shaping the composition and distribution of the gut microbiota (17). Some bacterial pathogens possess endo-␤-N-acetylglucosaminidase enzymes that cleave the ␤-1,4 linkage of the core ChbNAc present in all N-glycoproteins, releasing the N-glycan moiety (18).…”
mentioning
confidence: 99%